Surface water retention systems for cattail production as a biofuel. (1st December 2017) - Berry, Pamela; Yassin, Fuad; Grosshans, Richard; Lindenschmidt, Karl-Erich
Abstract: Surface water retention systems act to reduce nutrient pollution by collecting excess nutrients within a watershed via runoff. Harvesting aquatic biomass, such as the invasive cattail, from retention systems removes nutrients absorbed by the plant from the ecosystem permanently. Harvested biomass can be used as a renewable energy source in place of fossil fuels, offsetting carbon emissions. The purpose of this research was to simulate cattail harvest from surface water retention systems to determine their ability to provide suitable growing conditions with annual fluctuations in water availability. The economic and environmental benefits associated with nutrient removal and carbon offsets were also calculated and monetized. A proposed upstream and existing downstream water retention system in southern Manitoba were modelled using a system dynamics model with streamflow inputs provided by a physical hydrologic model, Modélisation Environmentale Communautaire - Surface and Hydrology (MESH). Harvesting cattail and other unconventional feedstocks, such as reeds, sedges, and grasses, from retention systems provided a viable revenue stream for landowners over a ten-year period. This practice generates income for landowners via biomass and carbon credit production on otherwise underutilized marginal cropland invaded with cattail. The economic benefits promote wetland habitat restoration while managing cattail growth to maintain biodiversity. Excess nitrogen and phosphorus are also removed from the ecosystem, reducing downstream nutrient loading. Utilizing surface water retention systems for cattail harvest is a best management strategy for nutrient retention on the landscape and improving agricultural resilience. Highlights: Cattail harvest from cattail invaded marginal cropland is a viable revenue stream. This practice generates income for landowners on underutilized marginal cropland. Cattail harvest also extracts excess nutrients from the aquatic ecosystem. Using surface water retention systems for cattail harvest increases nutrient removal. The economic benefits promote wetland habitat restoration and manage cattail growth.